2019
DOI: 10.1371/journal.pgen.1008073
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of gut microbiota composition and bile acid profiles in mice

Abstract: The microbial communities that inhabit the distal gut of humans and other mammals exhibit large inter-individual variation. While host genetics is a known factor that influences gut microbiota composition, the mechanisms underlying this variation remain largely unknown. Bile acids (BAs) are hormones that are produced by the host and chemically modified by gut bacteria. BAs serve as environmental cues and nutrients to microbes, but they can also have antibacterial effects. We hypothesized that host genetic vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 95 publications
2
63
0
Order By: Relevance
“…Several of the core taxa identified in this study are currently being studied as important modulators of host physiology. Turicibacter (0.02-5.50% total reads/input group) is a highly heritable genus of bacteria that is able to interact with host-derived bile acids and play a role in the neurotransmitter regulation in the mammalian gut [50,51]. Romboutsia (1.15-19.34% total reads/input group) appeared as the second most highly abundant genera throughout the study, and was identified as a member of the core microbiota in both trials.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the core taxa identified in this study are currently being studied as important modulators of host physiology. Turicibacter (0.02-5.50% total reads/input group) is a highly heritable genus of bacteria that is able to interact with host-derived bile acids and play a role in the neurotransmitter regulation in the mammalian gut [50,51]. Romboutsia (1.15-19.34% total reads/input group) appeared as the second most highly abundant genera throughout the study, and was identified as a member of the core microbiota in both trials.…”
Section: Discussionmentioning
confidence: 99%
“…Erysipelotrichales (including Turicibacter spp.) in the mouse ileum and cecum have been shown to be positively correlated with unconjugated ileal and cecal [62] and plasma [63] bile acids. Bacteroidales (including Muribaculum spp.)…”
Section: Self-reinoculation and Microbial Ecology In The Mouse Gitmentioning
confidence: 97%
“…Based on the data from the Metastats analysis on 40 bacteria at the genus level ( Table 2 ), among the 20 bacteria that were increased in NMOSD patients ( Table 2 , orders 1–20), including some short chain fatty acids-producing bacteria ( 19 22 ) ( Faecalibacterium , Roseburia , Coprococcus , Ruminococcaceae , Lachnospira ), which have protective role in colonic inflammation, and some proinflammatory bacteria, such as Granulicatella ( 23 ), Streptococcus ( 24 ), Proteus ( 25 ), and Desulfovibrio ( 26 ). Among the 20 bacteria that were decreased in NMOSD patients, most are conventional intestinal bacteria, and many are beneficial bacteria such as Rahnella ( 27 ), Lactococcus ( 28 ), Leptotrichia ( 29 ) and Turicibacter ( 30 ) ( Table 2 , orders 21–40). Granulicatella and Streptococcus , two well-studied bacteria, were significantly increased in NMOSD patients compared with HC subjects ( Figure 1E , p < 0.01 and Figure 1F , p < 0.05, respectively).…”
Section: Resultsmentioning
confidence: 99%